2007
DOI: 10.1042/bst0351122
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 and inflammatory neurodegeneration

Abstract: Inflammation occurs rapidly in response to acute brain insults such as stroke, haemorrhage or trauma, and can be sustained for long periods of time, for example in Alzheimer's or Parkinson's diseases and multiple sclerosis. Experimental evidence indicates that inflammation plays a major role in neurodegeneration under these conditions, and that the cytokine IL-1 (interleukin-1) is a pivotal mediator. IL-1 is expressed rapidly in response to neuronal injury, predominantly by microglia, and elevated levels of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
154
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(168 citation statements)
references
References 50 publications
(50 reference statements)
4
154
0
2
Order By: Relevance
“…8 Previously, we demonstrated reactivation of a focal myelin oligodendrocyte glycoprotein-induced experimental allergic encephalomyelitis lesion in the rat brain following systemic bacterial endotoxin injection. 9 Our findings parallel the disease-modifying effects of systemic inflammation on chronic neurodegeneration in models of Prion disease, 10 stroke, [11][12][13] MS, 14 and Parkinson's disease. 15,16 These findings together highlight an important generic role for innate immune-brain interactions in acute and chronic neurological dysfunction.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…8 Previously, we demonstrated reactivation of a focal myelin oligodendrocyte glycoprotein-induced experimental allergic encephalomyelitis lesion in the rat brain following systemic bacterial endotoxin injection. 9 Our findings parallel the disease-modifying effects of systemic inflammation on chronic neurodegeneration in models of Prion disease, 10 stroke, [11][12][13] MS, 14 and Parkinson's disease. 15,16 These findings together highlight an important generic role for innate immune-brain interactions in acute and chronic neurological dysfunction.…”
Section: Introductionsupporting
confidence: 65%
“…Interestingly, recent studies have shown that experimental stroke in mice induces a systemic inflammatory response that precedes an inflammatory response in the brain, with a strong contributory role for the chemokine CXCL-1. 38 Other recent studies have shown that peripheral IL-1b challenge exacerbates injury via a mechanism that is neutrophildependent after experimental stroke in mice 11 and that microglia/ macrophages, associated with EAE lesions in rat, respond to circulating cytokines, and produced in response to an inflammatory event lead to tissue damage and axon injury. 14 Effect of AdIL-1b on Magnetic Resonance Imaging Signal Changes To use clinically applicable measures of lesion reactivation rCBV, MTR and tissue water diffusion were measured by MRI over a 5-day period after injection of AdIL-1b, during which time systemic expression of IL-1b is maximal.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory models of neurodegeneration propose that systemic inflammation is negatively associated with cognition via increases in neuro-inflammation. Inflammatory cytokines -including Tumor Necrosis Factor(TNF)α, Interleukin(IL)-1β, and IL-6 -secreted by microglia in the brain likely establish and maintain neuro-inflammation (Glass, Saijo, Winner, Marchetto, & Gage, 2010), which can leads to neuronal apoptosis over the long-term (McCoy & Tansey, 2008;Simi, Tsakiri, Wang, & Rothwell, 2007), and inhibits neurogenesis in adults (Ekdahl, Claasen, Bonde, Kokaia, & Lindvall, 2003). Systemic inflammation in the periphery is tied to neuro-inflammation in neurodegenerative disorders (Perry, 2004), as well as in aging populations more generally (Perry, 2010).…”
Section: Inflammation and Cognitive Declinementioning
confidence: 99%
“…IL-1 is known to affect neuroimmune communication via brain endothelial cells (16,17), modulate brain inflammation via astrocytes (18) and microglia (19), and influence learning and memory via hippocampal neurons (20,21). The presence of IL-1 receptors in the brain was first demonstrated by binding studies that showed that IL-1 binds to specific structures in the brain including dentate gyrus granule cells, choroid plexus, and brain vasculature (22).…”
Section: Discussionmentioning
confidence: 99%